2020
DOI: 10.1128/iai.00573-19
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Development and Assessment of Viral Vectors Expressing a Fusion Antigen of Plasmodium falciparum LSA1 and LSAP2 for Efficacy against Liver-Stage Malaria

Abstract: Despite promising progress in malaria vaccine development in recent years, an efficacious subunit vaccine against Plasmodium falciparum remains to be licensed and deployed. Cell-mediated protection from liver-stage malaria relies on a sufficient number of antigen-specific T cells reaching the liver during the time that parasites are present. A single vaccine expressing two antigens could potentially increase both the size and breadth of the antigen-specific response while halving vaccine production costs. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 53 publications
(62 reference statements)
0
11
0
Order By: Relevance
“…More recently, a viral-vectored malaria vaccine that combined Pf TRAP with the highly conserved merozoite proteins, liver-stage antigen 1 (LSA1) and the liver-stage-associated protein 2 (LSAP2), was developed. Nevertheless, neither its immunogenicity nor protective efficacy were significantly impacted with the inclusion of these two proteins [ 59 , 60 , 61 ].…”
Section: Subunit Vaccinesmentioning
confidence: 99%
“…More recently, a viral-vectored malaria vaccine that combined Pf TRAP with the highly conserved merozoite proteins, liver-stage antigen 1 (LSA1) and the liver-stage-associated protein 2 (LSAP2), was developed. Nevertheless, neither its immunogenicity nor protective efficacy were significantly impacted with the inclusion of these two proteins [ 59 , 60 , 61 ].…”
Section: Subunit Vaccinesmentioning
confidence: 99%
“…When T cells lack CXCR6, a cell surface marker highly expressed by liver-infiltrating CD8 T cells, there is a reduction of liver-associated memory and sporozoite immunity [22]. Very recent studies (including this report) support that CD8 tissue resident memory T cells appear important for targeting of LS malaria following vaccination [23][24][25]. It appears that LS antigens represent important candidates for inducing protective CD8+ T cell responses in the attenuated sporozoite model.…”
Section: Introductionmentioning
confidence: 55%
“…Pre-erythrocytic subunit vaccines in clinical development have shown limited success in clinical trials. Several studies have reported that T cell immunity to LS antigens contributes to protective immunity [14,15,[23][24][25], suggesting that a combination vaccine approach targeting multiple life-cycle stages of the Plasmodium parasite may be important. Synthetic DNA delivered by adaptive electroporation (EP) is a particularly attractive vaccine platform for targeting LS antigens because of its ability to induce robust CD8+ T cell responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PfLSA-1 is high conserved in P. falciparum and is found in parasitophorous vacuole in the liver stage of the parasites. PfLSA-1 contains 17 amino acids repeats and is associated with the late liver schizont stage [105,106]. LSA-1 can induce IgG and IgM antibodies as well as CD4+ T cell production [105,107].…”
Section: Pflsa-1 and Pflsa-3mentioning
confidence: 99%